2009
DOI: 10.1002/ird.527
|View full text |Cite
|
Sign up to set email alerts
|

On the difficulty of managing an invisible resource: Farmers' strategies and perceptions of groundwater use, field evidence from Morocco

Abstract: In Morocco, many farmers rely on groundwater for irrigation. Extensive groundwater exploitation along with the recent droughts, have led to over-exploitation of this resource. We argue that state regulation is necessary but insufficient to manage groundwater. This article determines farmers' strategies in the exploitation of groundwater and explores the perceptions of farmers of the functioning of aquifers and the use of groundwater. We showed that farmers are rather pessimistic about the possibility of stoppi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 8 publications
(3 reference statements)
0
16
0
4
Order By: Relevance
“…However, groundwater research has focused mostly on the resource, rather than the actors who use and manage the resource (Hammani et al 2009). Bekkar et al (2009), Kuehne et al (2008) and Albrecht (1990Albrecht ( , 1995 are some of the small set of researchers who have explored the links between landholder behaviour and influences on landholder adoption in the groundwater context. Engaging rural landholders in practice change is complex and difficult, not least because there is a potentially large set of factors (personal, societal) influencing their decisions (Mazur et al 2013;Pannell et al 2006); and these vary according to each technology, each landholder, each farming context and over time (Curtis and Mendham 2011).…”
Section: Influencing the Use And Management Of Land And Water By Ruramentioning
confidence: 99%
“…However, groundwater research has focused mostly on the resource, rather than the actors who use and manage the resource (Hammani et al 2009). Bekkar et al (2009), Kuehne et al (2008) and Albrecht (1990Albrecht ( , 1995 are some of the small set of researchers who have explored the links between landholder behaviour and influences on landholder adoption in the groundwater context. Engaging rural landholders in practice change is complex and difficult, not least because there is a potentially large set of factors (personal, societal) influencing their decisions (Mazur et al 2013;Pannell et al 2006); and these vary according to each technology, each landholder, each farming context and over time (Curtis and Mendham 2011).…”
Section: Influencing the Use And Management Of Land And Water By Ruramentioning
confidence: 99%
“…However, state control requires a high degree of state capacity to monitor groundwater levels and use by many dispersed users. Bekkar et al (2009) argue that state action is necessary but insufficient for effective groundwater management. Even where there is state capacity, additional community efforts are often needed for effective groundwater management (Mitchell et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, however, the success of such measures depends on farmers' decisions. Bekkar et al (2009), Kuper et al (2009), andFaysse et al (2014) found that interventions to help farmers understand the nature of groundwater resources and how their actions could affect the resource conditions could provide the basis for community responses. These interventions are examples of the kinds of social learning that that bring stakeholders together to develop the capacity and trust needed for collaboration, which Pahl-Wostl et al (2007, 2008 argue are increasingly important for water management.…”
Section: Introductionmentioning
confidence: 99%
“…Decision makers follow different approaches to conserve groundwater, either through the implementation of regulations or through a joint dialogue with groundwater users. Since groundwater policies have proven to be difficult to implement (Hammani et al, 2009;Bekkar et al, 2009;Macoun and El Nasser., 2000), stakeholder involvement and participatory approaches are found to be an alternative solution to natural resource management. Petit (2004) explains that it is often in a situation of water stress that local stakeholders recognize the common character of groundwater resources and try to find adapted solutions to over exploitation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the perception and understanding of problems related to groundwater over abstraction are key but appear to vary considerably between stakeholders (White and Kromm, 1995;Shah 1993;Hammani et al, 2009). In the case of the Tadla and Souss irrigation scheme in Morocco, farmers were shown to have a reasonable idea about functioning of the aquifers and the water balance (Bekkar et al, 2009). They were able to put in place defensive farm strategies through collective access to save water when problems with groundwater exploitation occurred.…”
Section: Introductionmentioning
confidence: 99%